Device Electromagnetic Characterization of GaAs MESFET Transistor - Houda Amri; Mourad Zaabat (My University, 2014)
In this paper, an electromagnetic study of MESFET transistor based on iterative method is presented. This method is generating the relationship between the incident and reflected waves from the planar circuits. The WCIP method is developed from the fast modal transform algorithm.